DAMPAK RELOKASI PEDAGANG KULINER KAKI LIMA TERHADAP EKONOMI KELUARGA DI KECAMATAN TAMPAN - Rohma, Nur Afida; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted in Simpang Baru Village, Tuah Karya, Tampan District, JL.HR. Soebrantas. This study aims to find out the impact of relocation for street food vendors and to find out the strategy of street food vendors in maintaining the economic condition of the family after the relocation. Researchers used non probality sampling techniques. This study used sampling quota technique then took only 30% of the population of 350 which is 105 samples of street vendors in JL. Narrated by. Soebrantas, what's going on? The author uses descriptive quantitative methods and data instruments are questionnaires and documentation. The study found that pearson product correlation coefficient at the time of relocation impact was .690**. This means that the coefficient or relationship between the Impact of Street Vendors Relocation is 0.690 or the resulting impact of relocation is high. if the probability > is 0.05 then Ho is accepted, while if the < is 0.05 then Ho is rejected. Based on the table data above, correlation coefficient of 0.690 can be seen in the range of 0.62 to 0.80 which is highly categorized. This means that relocation has an impact on the economy of street food vendors.Keywords :, Street vendors, Reloxy, Culinary